Peningkatan UX Melalui Perancangan dan Pengujian Sistem Pembelajaran Digital Berbasis Buku menggunakan Design Thinking - Dian Ayu Cahyani; Irma Santikarama; Sigit Anggoro (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2025)
User Experience (UX) is a crucial aspect in determining the effectiveness of digital learning systems. This study aims to design and evaluate a book-based digital learning system prototype using the Design Thinking approach. The research was conducted through five stages: Empathize, Define, Ideate, Prototype, and Test. Data were collected using questionnaires, interviews, and observations involving students, lecturers, and publishers. The evaluation applied a triangulation strategy combining the System Usability Scale (SUS), heatmap analysis, and semi-structured interviews. The results indicate an average SUS score of 70, which is above the minimum benchmark of 68, although improvements are still needed in visual design and navigation. Heatmap analysis revealed that most navigation elements were successfully used, but some icons were not recognized and certain menus were rarely accessed. The interviews reinforced these findings, highlighting that the system supports lecturers in monitoring and enhances student engagement, yet issues remain regarding button color contrast, label consistency, and the speed of accessing large files. These results demonstrate that Design Thinking, when combined with triangulated evaluation, can produce a book-based digital learning system that is more interactive, adaptive, and collaborative. This study contributes to the literature by emphasizing that integrating user-centered design with triangulation methods can significantly improve UX quality in higher education digital learning contexts.